Identification of factors affecting the travel time reliability of public bus transportation - a case study along federal road F0050-route Kluang-A/Hitam-B/Pahat - Hareth A. Al-barakani,; Nasradeen A. Khalifa,; M. A. Alkubati,; Ahmed N. Al-Olof, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Public transportation provides basic mobility services to various types of facility actions including those involving education, employment, medical care, and recreation. The general goal of this study was to develop a model with respect to travel time. Public bus transport which connects two cities, A/Hitam- B/Pahat), was selected to conduct this study. Factors such as departure delays, route length, delays at marked traffic light intersections, delays at bus stops, and bus speeds were collected using observation methods. SPSS is a methodological tool used for statistical analysis. The results of the analysis showed a strong positive correlation of ‘0.942’ between travel time and route length, a moderate positive correlation of ‘0.697’ between travel time and delay at marked traffic light intersections, a weak correlation of ‘0.272’ between travel and departure time. delay with a significance level of 0.05. The determination coefficient showed a great regression explanatory power with R2 = 0.954. and (P <0.001). SPSS is also used to examine the data and generate models.